2018
DOI: 10.1111/jcmm.13902
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐17 family‐mediated regulation of Pknox1 influences hepatic steatosis and insulin signaling

Abstract: The aberrant expression of Pknox1 is associated with hepatic glucose and lipid dysmetabolism status of type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD). However, the underlying mechanism causing Pknox1 overexpression in this pathological status remains unclear. By using miRNA target prediction programs, we found that the 3′‐UTR of the Pknox1 mRNA sequence contains highly conserved target sites of miR‐17 family. In a rat model of streptozotocin and high‐fat diet‐induced T2DM and NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In a rat model of streptozotocin and high-fat diet-induced T2D, miR-17 family, especially miR-17, was also downregulated in the hepatocytes. Moreover, miR-17 overexpression enhanced insulin sensitivity in HepG2 and LO2 cells, characterized by altered phosphorylation on Insr signaling pathway proteins 62 . However, there was a study reporting that miR-17 impaired glucose metabolism by repressing Glut4 in SkM of a high-fat diet STZ-induced rat model and palmitic acid-exposed L6 rat skeletal muscle cell line 63 .…”
Section: Discussionmentioning
confidence: 97%
“…In a rat model of streptozotocin and high-fat diet-induced T2D, miR-17 family, especially miR-17, was also downregulated in the hepatocytes. Moreover, miR-17 overexpression enhanced insulin sensitivity in HepG2 and LO2 cells, characterized by altered phosphorylation on Insr signaling pathway proteins 62 . However, there was a study reporting that miR-17 impaired glucose metabolism by repressing Glut4 in SkM of a high-fat diet STZ-induced rat model and palmitic acid-exposed L6 rat skeletal muscle cell line 63 .…”
Section: Discussionmentioning
confidence: 97%
“…Small interfering RNA-mediated reduction of SRF in a rat insulinoma cell line partially inhibited the ability of these cells to respond to glucose [31]. The transcriptional regulator PKNOX1 is higher in the livers of diabetic and non-alcoholic fatty liver disease patients [32]. It was found that PKNOX1 could be regulated by miR-17 family members, including miR-17 and miR-20a [32].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional regulator PKNOX1 is higher in the livers of diabetic and non-alcoholic fatty liver disease patients [32]. It was found that PKNOX1 could be regulated by miR-17 family members, including miR-17 and miR-20a [32]. Overexpression of miR-17 and miR-20a in human hepatocytes increased the sensitivity of these cells to insulin and also decreased triglyceride and lipid accumulation [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the mature sequence and its ‘seed sequence’ of these four miRNAs were highly conserved among human, mouse, and pig based on identification of bioinformatics databases: miRbase [46], TargetScan [34], PicTar [43], PITA [36] and miRanda [44]. It is reported that miRNA-17 family plays a critical role in normal cardiac development, cardiovascular disease and polycystic kidney disease progression as well as affecting hepatic steatosis and insulin signaling [47,48,49,50,51,52]. Babu et al (2016) revealed that enhancing expression of miR-20a could decrease iron export and increase intracellular iron retention in lung cancer [32].…”
Section: Discussionmentioning
confidence: 99%